MEMBANGUN KEBERLANJUTAN USAHA KELOMPOK PENGRAJIN GENTA RATNA SARIN SEKAR KUNING, DESA BUDAGA, KABUPATEN SEMARAPURA - N. Paramananda; Ni Luh Putu Ratna Wahyu Lestari; Ida Ayu Agung Idawati (Universitas Triatma Mulya, 2024)
The superior and typical craft product of Budaga Village is the bell craft. The bells produced in Budaga Village are said to be superior because the quality of the typical bell crafts of Budaga Village is known to be very good based on the selection and mixture of raw materials used in the production process. The bell craft business that is engaged in by the majority of the people of Budaga Village is still classified as a Micro, Small and Medium Enterprise on a household industrial scale. Along the way, businesses with a small scope such as the bell craft business in Budaga Village often experience ups and downs in business. So far, the Ratna Sarin Sekar Kuning Bell Craftsmen Group has only marketed its products conventionally. Therefore, the community service team provides assistance and assistance related to online promotion training to increase the product's market share. The community service team also provides counseling on the importance of Occupational Health and Safety (K3), as well as assistance in making simple financial reports based on SAK-EMKM. With guidance and assistance in terms of good business management, craftsmen can manage their businesses more sustainably, both in terms of production, marketing, and financial management.